Electrocatalytic CO Reduction to Produce Long‐chain Products Through Fischer‐Tropsch Pathway - Bo Cao; Fu‐Zhi Li; Songbai Han; Qiang Xu; Jun Gu (ChemElectroChem)
Abstract Electrocatalytic CO reduction (COR) is a promising approach for converting C1 feedstock into valuable multi‐carbon fuels using renewable electricity. At ambient temperature, COR, particularly on Cu‐based catalysts, typically produces C2 chemicals as the dominant products, with long‐chain hydrocarbons containing more than five carbon atoms rarely forming. In contrast, Fischer‐Tropsch synthesis (FTS), a thermocatalytic process converting CO and H2, selectively generates long‐chain hydrocarbons. In this study, we utilized Ru nanoparticles for electrochemical COR under elevated conditions (423 K and 2.8 MPa). Long‐chain products with up to 21 carbon atoms were detected, achieving a Faradaic efficiency of 32 % and a weight selectivity of 65 % for C5+ products. We propose an FTS‐like pathway for this electrocatalytic process. Unlike thermocatalytic FTS, where adsorbed H atoms form via H2 dissociation, in this electrocatalytic version, the H atoms are generated through the Volmer reaction from water. Subsequently, the chemisorbed and activated CO species are hydrogenated, forming CHx intermediates that propagate into long‐chain products.